Education for all: an expanded vision - Fordham, Paul (UNESCO ParisFR, 1992)
Examines the equity issues relating to the education of girls and women. Looks at early childhood care and education and health and nutrition, and improving education and non-formal programmes for youth and adults in connection with broadening the means and scope of basic education. Emphasizes the need to encourage and facilitate the participation of families, communities and other factors in the provision of basic education.